#### Answer

(a) 3
(b) $x(x+1)^2$
(c) $\frac{-2x^{2}+1}{x(x+1)^{2}}$

#### Work Step by Step

(a) It has three terms, $\displaystyle \frac{1}{x}$, $-\frac{2}{(x+1)}$, and $-\frac{x}{(x+1)^{2}}$.
(b) The least common denominator of all the terms is: $x(x+1)^{2}.$
(c) $\displaystyle \frac{1}{x}-\frac{2}{(x+1)}-\frac{x}{(x+1)^{2}}=\frac{(x+1)^{2}}{x(x+1)^{2}}-\frac{2x(x+1)}{(x+1)}-\frac{x(x)}{(x+1)^{2}}=\frac{(x+1)^{2}-2x(x+1)-x^{2}}{x(x+1)^{2}}
=\frac{x^{2}+2x+1-2x^{2}-2x-x^{2}}{x(x+1)^{2}}=\frac{-2x^{2}+1}{x(x+1)^{2}}$